Funkcjonowanie niektórych obyczajów ludowych u Polaków z okolic Mościsk na Kresach południowo-wschodnich .......... 761 - Kostecka-Sadowa, Anna (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
THE FUNCTIONING OF CERTAIN FOLK CUSTOMS AMONG POLES FROM THE MOŚCISKA REGION IN THE SOUTH-EASTERN BORDERLANDS The article attempts to explore the transformation that occurred in rituals and old folk customs. The discussion is based on the observations of customs which were carried out for multiple years in several locations along the Polish-Ukrainian border. The dialectal expressions that constitute the basis of the article reveal that the past is clearly valuated. The changing civilisational, cultural, and mental landscape of the rural population serves as a document of an epoch that is fading away, and it is also important part of the national heritage.